2013
DOI: 10.3917/puf.meda.2013.01
|View full text |Cite
|
Sign up to set email alerts
|

Réinventer le travail

Abstract: Revenant sur l'histoire longue du travail, cet ouvrage éclaire la façon dont nos sociétés sont devenues des « sociétés fondées sur le travail » et les causes de cette évolution. Il présente ensuite les données les plus récentes sur l'importance que les Européens accordent aujourd'hui au travail, mais aussi sur la place que celui-ci occupe à côté d'autres sphères porteuses de sens pour eux (en particulier la famille). Il pointe la contradiction entre les immenses attentes projetées aujourd'hui par les individus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 0 publications
1
7
0
13
Order By: Relevance
“…This decision also demonstrated that work had become less central to their identity. Work remained important but other dimensions of their lives were also gaining in importance, a finding confirmed by other studies involving young workers (Méda and Vendramin, 2013;Mercure and Vultur, 2010). Work clearly constituted only one part of a much broader life plan for these young nurses, who valued work-life balance (Lavoie-Tremblay et al, 2010;Takase et al, 2009) and may have decided to leave their jobs when work began to spill over into their personal lives (Rhéaume et al, 2011b).…”
Section: Coping With the Challenges Of Nursingsupporting
confidence: 74%
“…This decision also demonstrated that work had become less central to their identity. Work remained important but other dimensions of their lives were also gaining in importance, a finding confirmed by other studies involving young workers (Méda and Vendramin, 2013;Mercure and Vultur, 2010). Work clearly constituted only one part of a much broader life plan for these young nurses, who valued work-life balance (Lavoie-Tremblay et al, 2010;Takase et al, 2009) and may have decided to leave their jobs when work began to spill over into their personal lives (Rhéaume et al, 2011b).…”
Section: Coping With the Challenges Of Nursingsupporting
confidence: 74%
“…Numerous studies have shown that the more importance people attach to work, the more (1) this sphere of activity represents a source of fulfilment that contributes to their identity and personal development, and the more (2) these people are likely to identify with their work [53,55,[67][68][69]. Accordingly, the unemployed older workers for whom identity destabilization is likely to be the most severe are those for whom work is a central pillar of identity, the place in their life in which they most invest [65,70,71].…”
Section: Relationship To Work and Identity Constructionmentioning
confidence: 99%
“…In Western countries, the loss of a job at this stage in life can be synonymous with long-term economic precariousness that are "expressive" [49,51,53], "experiential" [47], and "intrinsic" [48,54] are related to people's personal and social development (e.g., self-fulfilment). On the other hand, "instrumental", "economic", and "extrinsic" purposes [47,49,53] concern the more utilitarian aspects of work (e.g., something to do).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pour les catégories les plus favorisées, il s'agit surtout de « faire » un métier intéressant tandis que les caté-gories les moins favorisées aspirent à « avoir » un emploi qui conditionne l'accès aux ressources. Ce constat du début des années 2000 n'a pas été démenti par les enquêtes européennes : le travail et l'emploi occupent une place centrale, de manière particulièrement marquée en France (Méda et Vendramin, 2013).…”
Section: La Centralité De L'emploiunclassified